The Choir Church Model for Planting New Congregations in a Rural Context: Choral Director as Reflective Practitioner - Okpoti, Rebekah (Rural theology, 2025)
This article evaluates the choir church model for planting new congregations as implemented over a 15-month period in a rural high Anglican church in Lancashire, through the lens of the reflective journal kept by the choral director operating as ethnographer. The reflective journal was resourced by 30 semi-structured interviews and the experience of eight Choral Eucharists attended by clergy, choristers, governors, parents, and the school community. Insights from the reflective journal are set alongside the published objectives of the choir church model. The juxtaposition highlights the fragility of the choir church model as a church planting tool in a rural context.